Hemolysin coregulated protein 1 as a molecular gluing unit for the assembly of nanoparticle hybrid structures - Pham, Tuan Anh (Beilstein J Nanotechnol, 2016)
Hybrid nanoparticle (NP) structures containing organic building units such as polymers, peptides, DNA and proteins have great potential in biosensor and electronic applications. The nearly free modification of the polymer chain, the variation of the protein and DNA sequence and the implementation of functional moieties provide a great platform to create inorganic structures of different morphology, resulting in different optical and magnetic properties. Nevertheless, the design and modification of a protein structure with functional groups or sequences for the assembly of biohybrid materials is not trivial. This is mainly due to the sensitivity of its secondary, tertiary and quaternary structure to the changes in the interaction (e.g., hydrophobic, hydrophilic, electrostatic, chemical groups) between the protein subunits and the inorganic material. Here, we use hemolysin coregulated protein 1 (Hcp1) from Pseudomonas aeruginosa as a building and gluing unit for the formation of biohybrid structures by implementing cysteine anchoring points at defined positions on the protein rim (Hcp1_cys3). We successfully apply the Hcp1_cys3 gluing unit for the assembly of often linear, hybrid structures of plasmonic gold (Au NP), magnetite (Fe(3)O(4) NP), and cobalt ferrite nanoparticles (CoFe(2)O(4) NP). Furthermore, the assembly of Au NPs into linear structures using Hcp1_cys3 is investigated by UV–vis spectroscopy, TEM and cryo-TEM. One key parameter for the formation of Au NP assembly is the specific ionic strength in the mixture. The resulting network-like structure of Au NPs is characterized by Raman spectroscopy, showing surface-enhanced Raman scattering (SERS) by a factor of 8·10(4) and a stable secondary structure of the Hcp1_cys3 unit. In order to prove the catalytic performance of the gold hybrid structures, they are used as a catalyst in the reduction reaction of 4-nitrophenol showing similar catalytic activity as the pure Au NPs. To further extend the functionality of the Hcp1_cys3 gluing unit, Fe(3)O(4) and CoFe(2)O(4) NPs are aligned in a magnetic field and connected by utilization of cysteine-modified Hcp1. After lyophilization, a fiber-like material of micrometer scale length can be observed. The Fe(3)O(4) Hcp1_cys3 fibers show superparamagnetic behavior with a decreasing blocking temperature and an increasing remanent magnetization leading to a higher squareness value of the hysteresis curve. Thus the Hcp1_cys3 unit is shown to be very versatile in the formation of new biohybrid materials with enhanced magnetic, catalytic and optical properties.